Comparison Between Eracs and Non Eracs Methods on The Level of Pain and Mobilization in Post-Caesarean Section Patients - Millizia, Anna; Iqbal, Teuku Yudhi; Fadhilati, Nyak Intan (Fakultas Kedokteran Universitas Malikussaleh, 2023)
Enhanced Recovery After Caesarean Section (ERACS) is a post-cesarean recovery method that can provide faster functional recovery results and can minimize the occurrence of complications, and reduce hospitalization time. ERACS is considered to be able to reduce pain levels and accelerate early mobilization of patients after delivery better than the non-ERACS method. This study aims to compare ERACS and non-ERACS methods on the level of pain and mobilization in post-cesarean section patients. The method used in this study was observational analytic with a cross-sectional design carried out on 66 respondents at Abby Lhokseumawe Mother Children's Hospital. The results showed that there were differences between the ERACS and non-ERACS methods in terms of pain levels with a p-value of 0.010 (<0.005) and early mobilization with a p-value of 0.000 (<0.005) in post-cesarean section patients which can be concluded that delivery with the ERACS method is better in reducing the degree of pain and accelerating early mobilization compared to non-ERACS methods